Determinants of effective outsourced private security services by commercial banks in Nairobi, Kenya - Wachira Githae, Anthony Andrew; Theuri, Matthew Mwangi; Nyawira Kaguta, Ruth Joyce (Advances in Social Sciences Research Journal, 2018)
The study intended to examine the determinants of effective outsourced private security services by commercial banks in Nairobi, Kenya. The study aimed at exploring effectiveness of factors to consider, technology, relationship between vendor and other security stakeholders and challenges involved while procuring private security services to commercial banks. The study employed descriptive research design. The population of the study was 40 commercial banks in Kenya where a total population of 240 security officials employed in the security departments of the commercial banks was used. A sample of 150 respondents was picked. A questionnaire was used to collect primary data. Study results reveal that factors that the commercial bank considered before outsourcing private security services had a positive and significant effect on effectiveness of outsourced private security services by commercial banks. However, technology applied by the private security companies in providing security to commercial banks did not have a significant effect on effectiveness of outsourced private security services by commercial banks. Study findings further revealed that the relationship between the private security companies and other security stakeholders had a positive and significant effect on effectiveness of outsourced private security services by commercial banks. Additionally, study results show that challenges that emanate from outsourced private security services had a negative and significant effect on effectiveness of outsourced security services to commercial banks. The study recommends that the government should fast-track the private security regulations to enhance the quality and standard of private security services.